Intertask comparison of frontal plane knee position and moment in female athletes during three distinct movement tasks - Harty, C. M.; DuPont, C. E.; Chmielewski, T. L.; Mizner, R. L. (Scandinavian Journal of Medicine & Science in Sports, 2011)
Gender differences in dynamic frontal plane knee posture during functional tasks contribute to increased anterior cruciate ligament injury risk in female athletes. Many tasks have been used to assess frontal plane movement patterns, but few studies compare patterns across tasks or evaluate the influence of static alignment on dynamic postures. The purpose of our study was to (1) establish the intertask differences in frontal plane knee posture during step down, single leg land, and drop vertical jump tasks; (2) determine intra-athlete correlations in knee posture across tasks; and (3) investigate the intra-athlete correlations between frontal plane knee posture while standing and during movement. Thirty-seven female athletes from high demand sports participated in a motion analysis assessment. Substantial differences in the frontal plane knee angles and moments occurred between tasks. However, there were strong relationships in frontal plane knee angles (r=0.72-0.76) and moderate to good relationships in knee moments across tasks (r=0.426-0.627). No relationship existed between the standing and dynamic knee abduction angles (r<0.06). Female athletes who demonstrate at-risk knee position and loading are likely to do so across tasks. The lack of relationship between static and dynamic frontal plane knee posture suggests that neuromuscular mechanisms contribute to the consistency in movement patterns across tasks.